Juan Gabriel ARAYA. Nicanor in Chillán. Concepción, Ediciones Universidad del Bio-Bío, 2000, 139 pp (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
Without a doubt, an editorial effort is not only timely due to the circumstances that motivated its publication but also original and innovative due to the relationships that its author objectively established as a result of his research. It is not common to recreate the life and work of a writer relating him to the land where he was born and grew up and which witnessed the first phase of his existence, as a human being and as a professional being (Review)